Caries decline in the primary dentition of Belgian children over 15 years - Carvalho JC, D’Hoore W, Van Nieuwenhuysen JP. (Blackwell Synergy, 2004)
(1) To investigate changes in caries prevalence in the primary dentition of children resident in Brussels, Belgium between 1983 and 1998, (2) to analyse associations between changes in caries and children’s socioeconomic and ethnic aspects.